Quercetin prevents liver carcinogenesis by inducing cell cycle arrest, decreasing cell proliferation and enhancing apoptosis - Casella, María Laura (2014)
SCOPE: Quercetin is the most abundant flavonoid in human diet. It has special interest as it holds anticancerous properties. This study aims to clarify the mechanisms involved in quercetin effects during the occurrence of preneoplastic lesions in rat liver. METHODS AND RESULTS: Adult male Wistar rats were subjected to a two-phase model of hepatocarcinogenesis (initiated-promoted group). Initiated-promoted animals also received quercetin 10 and 20 mg/kg body weight (IPQ10 and IPQ20 groups, respectively). Antioxidant defenses were modified by quercetin administration at both doses. However, only IPQ20 group showed a reduction in number and volume of preneoplastic lesions. This group showed increased apoptosis and a reduction in the proliferative index. In addition, IPQ20 group displayed a reduction of cell percentages in G₁ and S phases, accumulation in G₂, and decrease in M phase, with reduced expression of cyclin D1, cyclin A, cyclin B, and cyclin-dependent kinase 1. Interestingly, peroxisome proliferator activated receptor-α levels were reduced in IPQ20 group. CONCLUSION: The outcomes of this study represent a significant contribution to the current understanding on the preventive mechanisms of quercetin during the early stages of liver cancer development, demonstrating that in addition to its known proapoptotic characteristics, the flavonoid modulates the expression of critical cell cycle regulators and peroxisome proliferator activated receptor-α activity.